Poor Efficiency of Eight-Plates in the Treatment of Lower Limb Discrepancy. Issue 7 (October 2016) - Gaumétou, Elodie; Mallet, Cindy; Souchet, Philippe; Mazda, Keyvan; Ilharreborde, Brice
Abstract : Background: Among the numerous existing epiphysiodesis procedures, the eight-plate–guided growth technique, initially described for angular deformities correction, has progressively gained popularity among pediatric orthopaedic surgeons to treat lower limb discrepancy (LLD). The goal of this study was to assess the efficacy of eight-plates in LLD. Methods: All children treated for LLD with eight-plates were prospectively included and followed until skeletal maturity. Efficacy of the epiphysiodesis was calculated 6 and 18 months postoperatively and at latest follow-up, according to a method previously validated for percutaneous epiphysiodesis using transphyseal screws (PETS). Radiologic measurements were performed using 3-dimensional low-dose stereoradiography. Intraoperative and postoperative complications were reported. Results: Thirty-two patients were included (average age at surgery, 12.5 y). For femoral epiphysiodesis, efficacy was only 23% at 6 months and 68% at latest follow-up. The procedure was even less efficient on the proximal tibia, with only 42% of the expected growth arrest at latest examination. Eight patients (20%) experienced plate-related pain during follow-up, and 5 physes (12.5%) required unplanned revision surgery. Conclusions: Results of the current series show that the eight-plate technique procedure was associated with few perioperative complications, but the growth arrest observed at follow-up was unpredictable and lower than that achieved with PETS in previous reports. Eight-plate procedures cannot be considered as an efficient epiphysiodesis technique in comparison with standard technique. Level of Evidence: Level IV.